Post-operative Emergence Agitation in Children Undergoing Inhalation General Anesthesia in Cipto Mangunkusumo Hospital: Study on Incidence and Affecting Factors - Wijaya, Andi Ade; Kapuangan, Christopher; Aktara, Betardi (Perdatin Pusat, 2015)
Emergence agitation (EA) during recovery from general anesthesia is often found among pediatric population. The etiology of EA in children is not fully understood. Possible risk factors include pre-school age, recent inhalation anesthetics, poor adaptability, and parental presence during recovery. The aim of the present study was to assess the incidence of EA and the affecting factors in children undergoing inhalation anesthesia in Cipto Mangunkusumo Hospital. There were 78 samples, aged 2–12 years undergoing inhalation anesthesia. Behavior during induction of anesthesia was assessed with Pediatric Anesthesia Behavior (PAB) score. In post anesthesia care unit (PACU) the incidence of EA was assessed with Aono’s four-point scale upon admission (T0), after 5 min (T5), 15 min (T15) and 30 min (T30). The incidence of EA in children undergoing inhalation anesthesia in this study was 39,7%. The incidence was higher in 2–5 years old children with PAB score 2 or 3. Midazolam, type of inhalation anesthetic agents and parental presence during recovery do not appear to have any bearing on the incidence of EA. Age of the children and the behavior during induction of anesthesia have a strong correlation with the incidence of EA.